Soluble Klotho Is Decreased in Children With Type 1 Diabetes and Correlated With Metabolic Control - Zubkiewicz-Kucharska, Agnieszka; Wikiera, Beata; Noczyńska, Anna (Frontiers in Endocrinology, 2021)
Klotho concentration may be considered as a prognostic factor in the development of chronic complications of diabetes. Moreover, decrease in sKlotho concentration may contribute to beta cell apoptosis and type 1 diabetes development. The aim of this study was to evaluate if sKlotho protein concentration in children with type 1 diabetes (T1D) and its correlation with classical risk factors of chronic complications of diabetes: dysglycemia and endothelial dysfunction. Material and methods: In a cross-section single center study the levels of soluble Klotho protein in 80 T1D (37 boys) and 34 healthy children (controls, 15 boys). Micro- and macroangiopathy were excluded and renal function was normal in all participants. Serum sKlotho, sICAM-1, sVCAM-1 and E-selectin levels were measured. Results: The concentration of sKlotho was lower in T1D than in the controls (2041.9±1017.6 pg/mL vs. 2790.3±1423.9 pg/mL, p=0.0113). sICAM-1, sVCAM-1 and E-selectin concentrations were comparable in patients and controls. In T1D, sKlotho was not correlated with the duration of diabetes. Klotho and E-selectin were correlated with HbA1c (r=-0.31, P=0.0066 and r=0.25, P=0.0351, respectively), but not with AVBG and blood glucose SD. Correlations of sKlotho with total cholesterol (r=0.31, P=0.0129), HDL-cholesterol (r=0.43, P=0.0011) and LDL-cholesterol (r=0.28, P=0.0412), but not with triglycerides, were found. Likewise, Klotho was not correlated with sICAM-1, sVCAM-1, and E-selectin concentrations. Conclusions: This study reports the significantly lower level of s-Klotho in children with type 1 diabetes, correlated with HbA1c and HDL cholesterol, but not with the adhesion molecules concentrations nor the duration of the disease. Negative correlation between the levels of HbA1c and soluble Klotho may suggest its possible involvement in the development of chronic diabetes complications.